ANALISIS PENGGUNAAN AUDIO UNTUK ANAK TUNANETRA DI Indonesia - Fornia, S.I.Kom, M.I.Kom, Fornia, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2023)
People who're blind are not able to see (absolutely blind) and might handiest see light (much less alert). Audio media that emphasizes listening to can useful resource human beings with imaginative and prescient problems. When blind youngsters are uncovered to this media on a normal basis, they expand extraordinarily touchy listening to. Using audio sources, this extraordinarily touchy listening to may be exploited for learning. Because blind junior high school kids have a stronger attention span than regular high school students, this medium may be appropriate for them if employed as a medium. With the help of junior excessive college pupils who are blind, this medium will resource inside the learning and obtaining of material. Audio The goal of this paper is to investigate the feasibility and usability of using audio media as a teaching tool for blind junior high school pupils. This study draws on some previous research that may be relevant to the study's title. According to preliminary studies, when blind college students use audio media, they are more motivated and can learn more easily. They can also analyze and interpret sounds heard through audio so that blind college students can better comprehend the material presented.